Exploring a New Therapy for Diabetic Polyneuropathy – The Application of Stem Cell Transplantation - Mizukami, Hiroki; Yagihashi, Soroku (Frontiers in Endocrinology, 2014)
Diabetic polyneuropathy (DPN) is the most common complication that emerges early in diabetic patients. Intervention with strict blood glucose control or treatment with aldose reductase inhibitor is reported to be effective in early stages of DPN. Curative treatment for overt or symptomatic DPN, however, has not been established, thus requiring much effort to explore a new therapy. Recent preclinical studies on the use of gene or cell therapy have provided promising results in the treatment of DPN. Of particular interest, induced pluripotent stem (iPS) cells are introduced. In these studies, restoration of DPN was proposed to be attributed to either neurotrophic factors released from transplanted stem cells or differentiation of stem cells to substitute the damaged peripheral nerve. There are still several problems, however, that remain to be overcome, such as perturbed function, fragility or limited survival of transplanted cells in diabetes milieu and risk for malignant transformation of transplanted cells. Questions, which cell is the most appropriate as the source for cell therapy, or which site is the best for transplantation to obtain the most effective results, remain to be answered. In this communication, we overview the current status of preclinical studies on the cell therapy for DPN and discuss the future prospect.